Human Immunodeficiency Virus-Induced Apoptosis of Human Breast Cancer Cells Via CXCR4 is Mediated by the Viral Envelope Protein But Does Not Require CD4 - Misumi, Shogo; Endo, Masafumi; Inatsu, Asako; Hashimoto, Koji; Takamune, Nobutoki; Shoji, Shozo (Current HIV Research, 2008)
HIV-1 infection results in an increased risk of malignancy as well as immune suppression. However, analyses of cancer incidence in chronically immunosuppressed transplant recipients and HIV-infected person have demonstrated an unexpected low incidence of certain types of cancer, such as breast cancers, and the mechanism behind this remains unclarified. In this study, we show that most breast cancer cell lines express CXCR4 but are not susceptible to HIV-1 infection. The apoptosis of breast cancer cells is induced by HIV-1 in a viral-dose- and time-dependent manner without productive infection. The apoptosis is induced by R5X4 and X4 HIV-1 but not by R5 HIV-1, and is inhibited by an anti- CXCR4 antibody, an anti-gp120 antibody, AMD3100, or pertussis toxin. The apoptosis is mediated via CXCR4 in breast cancer cells that exhibit conformational heterogeneity in comparison with CXCR4 in T-cells. Furthermore, the gp120 mutant (E370R) with a low CD4 binding ability can specifically induce apoptosis in breast cancer cells but not in T-cells. Taken together, these results indicate that HIV-1 and gp120 can induce breast cancer cell apoptosis through gp120- CXCR4 interaction without a CD4-induced conformational change of gp120, and may lead to a novel HIV-1-based therapy for breast cancer.
Keywords: apoptosis